2011
DOI: 10.1111/j.1466-8238.2011.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

The species richness–productivity relationship in the herb layer of European deciduous forests

Abstract: Aim  In contrast to non‐forest vegetation, the species richness–productivity (SR‐P) relationship in forests still remains insufficiently explored. Several studies have focused on the diversity of the tree layer, but the species richness of temperate deciduous forests is mainly determined by their species‐rich herb layer. The factors controlling herb‐layer productivity may differ from those affecting tree layers or open herbaceous vegetation, and thus the SR‐P relationship and its underlying processes may diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 51 publications
4
63
1
Order By: Relevance
“…Shackleton, 2000;Pokorny et al, 2004;Uys, 2006;Jacobs and Naiman, 2008;Bond and Parr, 2010;Pavlovic et al, 2011;Axmanová et al, 2012;Van Coller et al, 2013;Koerner et al, 2014;Scott-Shaw and Morris, 2014). Herbaceous species diversity studies along catenal zones suggest that disturbance and resource availability interact to shape diversity patterns in savanna ecosystems, although diversity is consistently higher in the eutrophic bottomlands (Shackleton, 2000;Stromberg, 2007).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Shackleton, 2000;Pokorny et al, 2004;Uys, 2006;Jacobs and Naiman, 2008;Bond and Parr, 2010;Pavlovic et al, 2011;Axmanová et al, 2012;Van Coller et al, 2013;Koerner et al, 2014;Scott-Shaw and Morris, 2014). Herbaceous species diversity studies along catenal zones suggest that disturbance and resource availability interact to shape diversity patterns in savanna ecosystems, although diversity is consistently higher in the eutrophic bottomlands (Shackleton, 2000;Stromberg, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…For this reason, savanna management models exclusively used grass species, particularly due to their significant contribution to total standing biomass and their important role in forage for both ruminant and non-ruminant savanna grazers (Treydte et al, 2013). Herbaceous dicotyledonous species, non-graminoid monocots and geophytes (collectively termed 'forbs' hereafter) have been ignored or merely lumped into a 'non-grassy, Increaser II' category in management models (Scott-Shaw and Morris, 2014), although they constitute the largest component of herbaceous species richness in grasslands (Pokorny et al, 2004;Bond and Parr, 2010;Koerner et al, 2014;Scott-Shaw and Morris, 2014), temperate deciduous forests (Axmanová et al, 2012) and savanna ecosystems (Shackleton, 2000;Uys, 2006;Jacobs and Naiman, 2008;Pavlovic et al, 2011;Van Coller et al, 2013). In a study on savanna browser resource use, Du Toit (1988) reported that forbs constitute between 50% and 80% of the diet of three savanna mesoherbivores (measured in terms of feeding time allocation of kudu, impala and steenbok).…”
Section: Introductionmentioning
confidence: 98%
“…negative relationship). Although many studies have explored the relationship between biomass and species richness specifically (Gough et al 1994;Guo and Berry 1998;Bhattarai et al 2004;Gillman and Wright 2006;Axmanová et al 2012), we include additional diversity measures to the model to better understand the ecosystem relationships. Understanding the relationship between biomass and species diversity (including richness) is essential to promote successful management, conservation and maintenance of ecosystem function and diversity (Michalet et al 2006), and to assist ecologists to understand the mechanisms that drive this relationship and inherently the sources of biodiversity (Mittelbach et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and observational biodiversity research recognized habitat productivity as one of the major determinants controlling local species richness of vascular plants (e.g., [4,5]). This relationship originally showed a typical hump-shaped pattern, i.e., the highest species richness is at the intermediate productivity level and gradually declined towards both marginal parts of the productivity gradient [6].…”
Section: Introductionmentioning
confidence: 99%